CHEMICAL COMPOSITION OF ESSENTIAL OILS OF EUGENIA CARYOPHYLLA AND MENTHA SP CF PIPERITA AND THEIR IN VITRO ANTIFUNGAL ACTIVITIES ON SIX HUMAN PATHOGENIC FUNGI - Nyegue, Maximilienne Ascension; Ndoyé-Foe, Florentine Marie-Chantal; Riwom, Sara Essama; Hockmeni, Christelle Tembiwe; Etoa, Francois-Xavier; Menut, Chantal (African Journal of Traditional, Complementary and Alternative Medicines, 2014)
Background: Many fungal infections are responsible for human skin damages, to control their negative action, some aromatic and medicinal plants are traditionally used by local population in Cameroon. The present study was carried out to determine the chemical composition of essential oils of Eugenia caryophylla and Mentha sp cf piperita and their antifungal activity on some human pathogenic fungi. Materials and methods: Essential oils from Eugenia caryophylla and Mentha sp cf piperita were extracted by steam distillation using Clevenger apparatus and the antifungal activity was evaluated on six human pathogenic fungal strains; two yeasts (Candida albicans 1 and Candida albicans 2) and four dermatophytes (Tricophyton rubrum 1, T. rubrum 2, T. violaceum, and T. soudanensis) using modified broth microdilution method M27-A3 and M38-A respectively. Results: The essential oils obtained yielded of 5.9 for Eugenia caryophylla and 0.2% Mentha sp cf piperita respectively. The chemical composition was assigned by GC and GC/SM and showed that E. caryophylla was mainly composed of eugenol (80.0 %), -caryophyllene (8.3%), and eugenol acetate (6.7%) while Mentha sp cf piperita was characterized by piperitone (67.5 %), menthol (10.0 %) and ß-phellandrene (5.8%). The result showed that essential oil of E. caryophylla exhibit the highest antifungal activity with MICs and MFC of 0.25µL/mL and 0.125µL/mL for filamentous fungi and MIC of 0.5 µL/mL for both yeast strains while MFC value was 1 µL/mL for one yeast strain and not determined for the second. MFCs Mentha sp cf piperita essential oil showed a weak activity with a MIC of 2.5 µL/mL on Tricophyton strains while no activity was exhibited on Candida albicans strains. Conclusion: The results of this work can be used to confirm their traditional uses and can also be proposed as natural ingredients to some industries to treat superficial infections.